ISDEV USM AND UNISSA AIM TO REALISE A 'NATION OF HYMNS' - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 March 2016 – The Centre for Islamic Development Management Studies (ISDEV) Universiti Sains Malaysia (USM) is joining hands to realise the hopes of Brunei Darussalam to become a ‘Nation of Hymns’ by upholding Islam as the primary belief and reference system in life, with the society and the leaders always in remembrance of Allah Almighty.